Influence of Smartphone Usage on Health Causing Insomnia and Binge Eating: Smartphone Usage, Insomnia & Binge Eating - Aslam, Maria; Dur e Najaf, Syeda; Arooj, Fiza; Rai, Sadia Asad; Abdul Manan, Alina; Fatima, Sehar (Pakistan BioMedical Journal, 2021)
Smart phone is an electrical device and its use is increasing day by day even in the growing countries like Pakistan. Difficulty in sleeping and disturbed sleep quality is termed as insomnia and binge eating is a psychological disorder characterized by overeating. Objective: To access the influence of excessive use of smart phone on health causing insomnia and binge eating. Method: A Cross Sectional Study design was done on 100 university students in Lahore to elucidate the influence of smart phone usage on health causing binge eating and insomnia. A self-formulated questionnaire was used including questions like (age, sex, weight, height, snacking while using smart phone and sleep quality). Purposive Sampling technique was used to collect data. Adolescent’s aging 20-25 years of age were participants of the study. Data was analyzed through latest version of SPSS. Result: According to the findings of study, out of total 100 participants 69 were females and 31 were males. Majority 61% of the participants were having disturbed sleep quality due to smart phone usage and 64% were binging while on their smart phones using social media. Conclusion: It is concluded from study that percentage of smart phone usage is contributing to sleep disturbances and high calorie intake in university students.The results suggest that students who were addicted to smartphones were having sleep disturbances and were also binging. In addition, it was also Affecting their weight as their BMI were increased.